Grammatical Mistakes of Indonesian-English Translation on Students’ Thesis Abstracts - Iis Sujarwati; Muthia Hamidah (IKIP PGRI Bojonegoro, 2022)
Abstract: The study aimed to knowing the grammatical mistakes found in students’ translation texts especially in the thesis abstract made by students of the Business and Economy Faculty of Bengkulu University. It investigated how the grammatical rules were implemented in their thesis abstracts. The study used the analysis of English grammar rules based on grammatical theories. The documents were used as the main data in this study, there were ten thesis abstracts made by the students. The results showed that there were 38 grammatical mistakes found. The most frequent grammatical mistakes made by students were word choice, word order, verb + agreement, and tenses. Then, at the end of the analysis, researchers gave the model of improvement based on the grammatical rules toward the grammatical mistakes that researchers found. This step was very important because the translation was about how we transferred the source language to the target language in equal meaning. Abstak: Studi ini bertujuan untuk mengetahui kesalahan tata bahasa yang ditemukan pada teks terjemahan mahasiswa khususnya pada abstrak skripsi yang dibuat oleh mahasiswa Fakultas Bisnis dan Ekonomi Universitas Bengkulu. Ini memeriksa bagaimana aturan tata bahasa diterapkan dalam abstrak tesis mereka. Penelitian ini menggunakan analisis aturan tata bahasa Inggris berdasarkan teori tata bahasa. Data utama dalam penelitian ini berbentuk dokumen, yaitu sepuluh abstrak skripsi yang dibuat oleh mahasiswa. Hasil penelitian menunjukkan bahwa terdapat 38 kesalahan tata bahasa. Kesalahan tata bahasa yang paling banyak ditemukan adalah pilihan kata, urutan kata, kata kerja + agreement, dan tenses. Kemudian, pada akhir analisis, peneliti memberikan model perbaikan berdasarkan kaidah gramatikal terhadap kesalahan gramatikal yang peneliti temukan. Langkah ini sangat penting, karena penerjemahan adalah tentang bagaimana kita mentransfer bahasa sumber ke bahasa sasaran dalam arti yang setara.